2016
DOI: 10.1107/s205698901601536x
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-bonded network of trinuclear copper(II) 4-iodopyrazolate complexes formed by mutual breakdown of chloroform and nanojars

Abstract: Acidity created by the decomposition of chloro­form solvent leads to breakdown of (Bu4N)2[{CuII(μ-OH)(μ-4-I-pz)}nCO3] (n = 27–31) nanojars in a chloro­form/1,4-dioxane solution to the trinuclear complex (Bu4N)2[Cu3(μ 3-Cl)2(μ-4-I-pz)3Cl3]·0.5dioxane, which forms extended sheets based on C—I⋯Cl—Cu halogen bonding and C—H⋯Cl—Cu hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In recent years, a number of new noncovalent interactions have been described . Their naming is derived from the periodic table column associated with the Lewis acid atoms involved in the interaction: halogen, chalcogen, pnicogen, tetrel, , triel, , spodium, regium, alkali-earth, , and alkali bonds correspond to the interaction between an electron donor group and an atom in the Lewis acid that belongs to columns 16–11, 2 and 1 of the periodic table, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of new noncovalent interactions have been described . Their naming is derived from the periodic table column associated with the Lewis acid atoms involved in the interaction: halogen, chalcogen, pnicogen, tetrel, , triel, , spodium, regium, alkali-earth, , and alkali bonds correspond to the interaction between an electron donor group and an atom in the Lewis acid that belongs to columns 16–11, 2 and 1 of the periodic table, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles can form structures of various nuclearities, ranging from mononuclear (Mighell et al, 1975;Liu et al, 2001;Małecka et al, 2003) to polynuclear complexes (He, 2011;Contaldi et al, 2009;Chandrasekhar et al, 2008) and metallacycles (Vynohradov et al, 2020a;Surmann et al, 2016;Galassi et al, 2012) with specific molecular topologies. By performing the synthesis of metal complexes by oxidative dissolution of metals, commonly known as direct synthesis (Kokozay et al, 2018;Plyuta et al, 2020;Sirenko et al, 2020;Li et al, 2021), copper can be introduced in a zerovalent state.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The search shows a total of thirteen crystal structures with the presence of halogen atoms in apical disposition interacting with copper (II) atoms linking the pyrazole rings. Of those structures, only one exhibited fluoride anions (CCDC refcode HUXWUU [94]), chloride is present in 10 crystal structures (JALKIT [95], OBOQAY [96], OBOQEC [96], OBOQIG [96], RETQIR [97], RUYGUN [98], RUYHAU [98], UWOMAW [99], VADYAB [100] and VAZCUX [101]) and bromide in two (ELODIS [102] and ELODOY [102]). It was observed that, in all these cases, two of the anions were simultaneously interacting with a single (Pz-M) 3 molecule in the apical position as shown in Figure 8.…”
Section: Csd Searchmentioning
confidence: 99%